2017
DOI: 10.1186/s13007-017-0200-8
|View full text |Cite
|
Sign up to set email alerts
|

A multiplex PCR for rapid identification of Brassica species in the triangle of U

Abstract: BackgroundWithin the Brassicaceae, six species from the genus Brassica are widely cultivated throughout the world as oilseed, condiment, fodder or vegetable crops. The genetic relationships among the six Brassica species are described by U’s triangle model. Extensive shared traits and diverse morphotypes among Brassica species make identification and classification based on phenotypic data alone challenging and unreliable, especially when dealing with large germplasm collections. Consequently, a major issue fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
1
16
0
2
Order By: Relevance
“…The amplified regions were compared with NCBI GenBank. Results confirmed all primer pair specificities (i.e., B. juncea and B. napus for A6, B. juncea and B. nigra for B, and B. napus for C1), showing a 100% identity to the target species with BLASTn analysis [20,21].…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…The amplified regions were compared with NCBI GenBank. Results confirmed all primer pair specificities (i.e., B. juncea and B. napus for A6, B. juncea and B. nigra for B, and B. napus for C1), showing a 100% identity to the target species with BLASTn analysis [20,21].…”
Section: Resultssupporting
confidence: 58%
“…In order to selectively distinguish each mustard species, three species-specific DNA regions were also considered (i.e., Bra019579 (Chromosome A6, 220 bp) specific for B. juncea and B. napus , pBNBH35 (Chromosome B, 280 bp) specific for B. juncea and B. nigra and Bo1g016520 (Chromosome C1, 130 bp) specific for B. napus ). These regions were previously identified by Koh et al [20] and Schelfhout et al [21]. All the primer pairs used in this study are reported in Table 1.…”
Section: Methodsmentioning
confidence: 66%
See 2 more Smart Citations
“…Oilseed rape (Brassica napus) is the second most important oilseed crop and belongs to the mustard family (Brassicaceae), which consists of 338 genera with more than 3,709 species cultivated worldwide, especially in temperate and mountainous regions (Al-Shehbaz et al, 2006;Warwick et al, 2010). B. napus is a relatively young crop species (AACC genome, 2n = 38) that derived from a spontaneous hybridization between B. rapa (AA genome, 2n = 20) and B. oleracea (CC genome, 2n = 18) (Koh et al, 2017). Europe, Canada, China, India, and Australia are the leading production zones with 25.5, 20.3, 13.3, 8.4, and 3.9 million metric tons of rapeseed production in 2018, respectively (FAO Database).…”
Section: Introductionmentioning
confidence: 99%